Patterns in random permutations avoiding the pattern 321. Issue 2 (14th November 2018) - Janson, Svante
Abstract : We consider a random permutation drawn from the set of321 ‐avoiding permutations of length n and show that the number of occurrences of another pattern σ has a limit distribution, after scaling by n m  +  ℓ where m is the length of σ and ℓ is the number of blocks in it. The limit is not normal, and can be expressed as a functional of a Brownian excursion.